"School banding": Principals' perspectives of teacher professional development in the school-based management context. Issue 6 (4th September 2017) - Lee, Daphnee Hui Lin; Chiu, Chi Shing
Abstract : Purpose: The purpose of this paper is to explore how principals' leadership approaches to teacher professional development arise from school banding and may impact upon teacher professional capital and student achievement. Design/methodology/approach: The case study is situated within the context of school-based management, comprising reflective accounts of nine school principals selected by stratified sampling from a sample of 56 Hong Kong schools to represent Bands One, Two, and Three schools. The reflective accounts were triangulated with observations of teachers and analysis of school websites. Findings: First, under school-based management, principals remain obliged to recognize the power of state-defined examinations in determining the schools' future priorities. Second, the exercise of school autonomy in response to this obligation varies, depending upon the competitive advantage schools have in the school banding system. Ideally, effective school-based management is dependent upon the principal's capacity to facilitate good instructional practices. However, principals need to adjust their leadership practices to school contextual demands. Third, adaptations to contexts result in the varied developments of teacher capacities in schools, corresponding with the types of principal leadership adopted. Originality/value: While statistical studies have identified attributes of exemplary principal leadership, few studies have examined the qualitative reasons for the exemplification of these attributes, and the influence of the school context in shaping these attributes. Departing from assumptions that leadership attributes are intrinsic to individuals, this paper considers how principals contextualize leadership in teacher professional development to the schools' student academic achievement.